=cos24-cos(24+60)-cos72
= cos 24-(cos 24 cos 60-sin 24 sin 60)-cos 72
=cos24-0.5cos24+ (root 3/2)*sin24-cos72
=0.5cos24+ (root 3/2)*sin24-cos72
=(cos24sin30+sin24cos30)-cos72
=sin54-cos72
=cos36-cos72
=cos36-(2(cos36)^2- 1)
=cos36-2(cos36)^2+ 1
= cos 36 *( 1-2 cos 36)+ 1 & lt; - 、
|
Establish an isosceles triangle ABC with A as the fixed point and ∠BAC=36 |
Then it is obvious that the base angles b and c are both 72 |
The bisector drawn from B intersects AC at point D, as shown in the following figure: |
A |
/ \ |
/ \ |
/ D |
/ \ |
B - C |
Abd ABD, BDC is isosceles triangle |
Now let AD= 1 |
Then |
AD=BD=BC= 1 |
AB=2cos36 |
DC=AB-AD=2cos36- 1 |
In triangle BDC, sine theorem |
DC BD |
- = - |
sin∠CBD sin∠C |
Bring the value in and get |
(2 cos 36- 1)/sin 36 = 1/sin 72 |
= & gt(2 cos 36- 1)* sin 72/sin 36 = 1 |
= & gt(2 cos 36- 1)* 2 cos 36 = 1 |
= & gt(2 cos 36- 1)* cos 36 = 0.5->; -& gt; /
Bring in the original formula
cos24 -sin6 -cos72 =0.5
Attachment: (Supplementary)
The above geometric algebra problem only applies to this problem.
Because the value of cos36 (or cos72) is not calculated in the solution;
If there is such a requirement, the following methods can be adopted: (Do not write the specific process)
First, calculate sin 18:
sin(2* 18)=cos(3* 18)
According to the triple angle formula
= & gt
2sin 18*cos 18=4(cos 18)^3-3cos 18
= & gt
4(sin 18)^2+2sin 18- 1=0
= & gt
Sin 18=[ (root number 5)- 1]/4.
= & gtSin36=[ root number (10-2 root number 5)]/4